François Jacob: Bricolage and the Possible. - Marks, John (Nottingham French Studies, 2020)
As well as his ground-breaking work in the field of molecular biology with Jacques Monod, François Jacob was a gifted and influential writer on science. His extraordinary capacity to make imaginative connections and to coin compelling metaphors informed both his work as a scientist and his writing on science. This article looks at the development of Jacob's distinctive constructivist conceptualization of science over the course of his career. Although Jacob was initially attracted to the metaphor of genetic material as a computer programme, he ultimately moved away from the mechanistic model of reproduction and evolution favoured by Monod. In a short paper published in the journal Science in 1977, he used the metaphor of bricolage as a way of conveying that biology evolution is a process of 'tinkering' with pre-existing materials rather than an elegant process of design. This conceptualization of the evolutionary process of building the new from the old has been highly influential in thinking on biology. In a more general sense, the concept of bricolage has a central role in Jacob's work, bringing together his thinking on evolution and science in general. The centrality of bricolage for Jacob positions him philosophically in many ways in the opposing camp to the Cartesian tradition, which was at the core of Monod's vision of science in the world.